Hubungan Penggunaan Multimedia dalam Pembelajaran terhadap Peningkatan Hasil Belajar Peserta Didik - Wahyudi Wahyudi; M. Daud Yahya; Jenuri Jenuri; Catur Budi Susilo; Dina Mayadiana Suwarma; Okta Veza (Departement of Mathematics Education, 2023)
This study discusses the impact of using multimedia in learning on improving students' learning outcomes. The research used a literature review method by examining various related studies that have been conducted. The analysis results showed that the use of multimedia can increase motivation, interest, and learning outcomes of students in learning. However, the effectiveness of multimedia use in learning depends on various factors such as multimedia design and content, teaching methods, student characteristics, and available learning environments. Therefore, the use of multimedia in learning requires a holistic and integrated approach. Continuous research and development are needed to improve multimedia design and use as well as to consider the influencing factors.